The influence of vancomycin on extracellular matrix and pro-inflammatory cytokine expression in human articular chondrocytes. (February 2018) - Chen, Yi-Ru; Chang, Jui-Hung; Yang, Kai-Chiang; Lu, Hsein-Kun; Senatov, Fedor Svyatoslavovich; Wu, Chang-Chin; Tsai, Mong-Hsun
Graphical abstract: Highlights: High dose of vancomycin (≥1000 μg/mL) has chondrotoxicity. Low dose of vancomycin (500 μg/mL) did not change the mRNA levels of ECMs and pro-inflammatory cytokines to chondrocytes. Vancomycin did not affect IκB to initiate the NF-κB pathway or COX-2 synthesis. Vancomycin at a low dosage did not have a deleterious effect on chondrocytes. Abstract: Intravenous infusion or intra-articular administration of vancomycin is widely used to treat septic arthritis. However, the cytotoxic effects of vancomycin at cellular and molecular levels have yet to be fully elucidated in chondrocytes. Primary human chondrocytes were cultured in media supplemented with vancomycin at a series of concentrations (0, 100, 500, 1000, and 5000 μg/mL) to study the dose-dependent toxicity. Since inflammatory chondrocytes are more catabolic than normal cells, the influence of vancomycin (500 μg/mL) on interleukin-1beta (IL-1β)-stimulated chondrocytes was evaluated. Exposure of chondrocytes to a high dose of vancomycin (≥1000 μg/mL) resulted in chondrotoxicity. Non-lethal dose of vancomycin (500 μg/mL) did not change the viability, morphology or glycosaminoglycan content of the normal or IL-1β-stimulated chondrocytes, or affect the mRNA levels of extracellular matrixes (aggrecan, collagen type I, II, and X) and pro-inflammatory cytokines (IL-1β, TNF-α, IL-6, IL-10, MMP-3, MMP-9, and TIMP-1). ELISA revealed that vancomycin exposure did not affect the levels of PGE2, IL-1β, MMP-3, or MMP-9 in normal and IL-1β-stimulated cells. Western blotting further showed that vancomycin did not affect IκB and p50 to initiate the NF- κ B pathway or COX-2 synthesis. Vancomycin at a low dose (500 μg/mL) did not have a deleterious effect on chondrocytes.